Peripheral Inhibitor of AChE, Neostigmine, Prevents the Inflammatory Dependent Suppression of GnRH/LH Secretion during the Follicular Phase of the Estrous Cycle. (15th August 2017) - Herman, Andrzej P.; Skipor, Janina; Krawczyńska, Agata; Bochenek, Joanna; Wojtulewicz, Karolina; Antushevich, Hanna; Herman, Anna; Paczesna, Kamila; Romanowicz, Katarzyna; Tomaszewska-Zaremba, Dorota
Abstract : The study was designed to test the hypothesis that the inhibition of acetylcholinesterase (AChE) activity at the periphery by Neostigmine (0.5 mg/animal) will be sufficient to prevent inflammatory dependent suppression of the gonadotropin-releasing hormone (GnRH)/luteinising hormone (LH) secretion in ewes in the follicular phase of the estrous cycle, and this effect will be comparable with the systemic AChE inhibitor, Donepezil (2.5 mg/animal). An immune/inflammatory challenge was induced by peripheral administration of lipopolysaccharide (LPS; 400 ng/kg). Peripheral treatment with Donepezil and Neostigmine prevented the LPS-induced decrease (P < 0.05 ) in LH β gene expression in the anterior pituitary gland (AP) and in LH release. Moreover, Donepezil completely abolished (P < 0.05 ) the suppressory effect of inflammation on GnRH synthesis in the preoptic area, when pretreatment with Neostigmine reduced (P < 0.05 ) the decrease in GnRH content in this hypothalamic structure. Moreover, administration of both AChE inhibitors diminished (P < 0.05 ) the inhibitory effect of LPS treatment on the expression of GnRH receptor in the AP. Our study shows that inflammatory dependent changes in the GnRH/LH secretion may be eliminated or reduced by AChE inhibitors suppressing inflammatory reaction only at the periphery such as Neostigmine, without the need for interfering in the central nervous system.